Effects of an “Internet +” Multidisciplinary Management Model Oriented by Nurse Specialists on Obesity Combined with Polycystic Ovary Syndrome - Yuyi Ou; Lixia Wu; Li Liu; Xiutao Ye; Yanjin Chen; Huizhi Yuan (Clinical and Experimental Obstetrics & Gynecology)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine metabolic disease in women of reproductive age, and its treatment mainly relies on adjusting lifestyle and oral drug therapy. With the development of the Internet and shared economy, the “Internet + nursing services” model has become increasingly popular, is presently an essential component of the Health Wellness project and has a promising future. Methods: This study involved 100 gynecological outpatients with PCOS from the Foshan Maternal and Child Health Hospital. They were divided into a control (routine nursing) and an experimental (“Internet +” multidisciplinary management oriented by nurse specialists) group according to a predefined nursing scheme. Several indicators, such as rates of ovulation and pregnancy, body mass index (BMI), waistline, serum hormone levels, metabolic indicators and psychological status of patients, were compared between the two groups before and half a year after the nursing intervention. Results: Six months after the intervention, the experimental group had significantly higher ovulation and pregnancy rates than the control group (88.00% vs. 68.00%, 48.00% vs. 22.00%, p < 0.05). Additionally, the experimental group showed a significant decrease in BMI, waistline, serum hormone levels (i.e., testosterone and luteinizing hormone [LH]) and homeostasis model assessment of insulin resistance (HOMA-IR) compared to the control group (p < 0.05). However, no obvious differences were observed in follicle-stimulating hormone (FSH) and fasting blood glucose (FBG) (p > 0.05) compared with the control group. Further, patients in the experimental group also displayed better psychological status, with a significant decrease in self-rating anxiety scale (SAS) scores and self-rating depression scale (SDS) half a year after intervention (p < 0.05). Conclusions: Interventions using the “Internet +” multidisciplinary management model oriented by nurse specialists not only effectively increased the rates of ovulation and pregnancy of PCOS patients but also significantly improved patients’ indicators such as BMI, waistline, serum hormone levels, metabolic indicators, and psychological status.